Revised values of the bond‐valence parameters for TeIV—O, TeVI—O and TeIV—Cl. (24th March 2013) - Mills, Stuart J.; Christy, Andrew G.
<x xml:space="preserve">Abstract</x> Bond‐valence parameters r0 and b have been re‐determined for TeIV—O: r0 = 1.9605 Å, b = 0.41; TeVI—O: r0 = 1.921 Å, b = 0.56; and TeIV—Cl: r0 = 2.3115 Å, b = 0.555. Bond distance data from 208 independent TeIV—O polyhedra, 118 TeVI—O polyhedra and 26 TeIV—Cl polyhedra were used, and all neighbours out to 3.5 Å were included. Root‐mean square deviations of bond‐valence sums on Te from ideal values were 0.1934, 0.1939 and 0.0865 v.u. The good fit for TeIV—O over a range of Te coordination numbers from 3 to 12 demonstrates that there is no essential difference in character between short `primary' Te—O bonds, oriented away from the Te lone pair, and longer `secondary' Te—O bonds on the same side of the Te atom as the lone pair. Comparison of bond‐valence sums for Te—O polyhedra obtained using the new parameters with those calculated using earlier literature values shows that the new parameters give a narrower spread of calculated bond‐valence sums, which means much closer to the formal valence for both oxidation states of tellurium.